Kaj se lahko naučimo od Jacquesa Mehlerja, klasičnega kognitivnega znanstvenika - Saksida, Amanda (Psihološka obzorja (Ljubljana), 2022)
The article shows the life work of one of the key fi gures of the so-called cognitive revolution, Jacques Mehler, who was one of the most successful European researchers in the fi eld of the development of the human mind, especially the development of language. The article presents the main assumptions of classical cognitive science – the modularity of the mind and the role of nature and nurture in the development and functioning of the mind – and describes which insights into the functioning of the mind have been enabled by Mehler’s empirical research over the past decades. New fi ndings that have changed cognitive science over the last two decades and that have partly infl uenced his work are also briefl y presented . The way in which Mehler has repeatedly integrated these new insights into his work can represent one of the models of the synthesis of empirical and theoretical research.
Keywords: classical cognitive science; cognitive science; Jacques Mehler; jezik; klasična kognitivna znanost; kognitivna znanost; language; language acquisition; Mehler, Jacques; mind; modularity of mind; modularnost uma; razvoj govora; um